Aggressive Digital Papillary Adenocarcinoma at Atypical Site. Issue 12 (February 2019) - Gupta, Jagdish; Gulati, Anchana; Gupta, Mudita; Gupta, Archit
Aggressive digital papillary adenocarcinoma (ADPA) is a rare tumour of eccrine origin. They present as asymptomatic nodules with flattened and thickened surface skin, most commonly on fingers and toes. It mimics many benign entities and tumours, hence leading to a delay in diagnosis. It has a high metastasizing potential, but is slowly progressive. Histopathologically, it has both a nodular and a cystic component with papillary projections into cystic spaces. We present a 54-year man with a tumorous mass on right heel, which was diagnosed by histopathology and immunohistochemistry as ADPA. Our case had ADPA lesion, a rarely reported malignancy on an uncommon site with distant metastasis.